Reducing Pangolin Demand by Understanding Motivations for Human Consumption in Guangdong, China - Zhang, Fuhua; Yu, Yishuang; Wu, Shibao; Mahmood, Amna; Yu, Jiaming; Min, Yue (Frontiers in Ecology and Evolution, 2020)
Pangolins are some of the most trafficked mammals in the world. China is a major destination country for illegal wildlife trade and Guangdong Province is one of the areas of high domestic wildlife consumption. A willingness to consume lies at the root of the illegal wildlife trade. To understand the ideological roots of pangolin consumption, and to propose solutions, we conducted a consumption survey in 21 prefecture-level cities in Guangdong and have collected 1957 valid questionnaires. In these questionnaires, 108 respondents (5.52%) who had consumed pangolin-related products, scales had been consumed by 61 respondents (3.12%), 58 respondents (2.96%) had consumed meat. We found that scale consumption was primarily motivated by disease treatment (80.43%). The main reason for meat consumption was accidental (44.83%), but among those who intentionally ate pangolin were motivated by curiosity (22.41%) or “showing off” (8.62%). Simultaneously, the respondents’ future consumption willingness for medicinal purposes was more difficult to change than its use for other purposes. What’s more, the public’s insufficient understanding of the status of pangolins in China and weak legal awareness were potential reasons for pangolin consumption. In addition to classifying pangolins as Category I state-protected animals in China and strengthening penalties and enforcement, we recommend creating public awareness of the risk of zoonotic diseases, advocating for the use of alternative medicines in disease treatment and removing scales from ingredients in patented medicines, which will all act to reduce the demand for pangolins. We expect these actions to change public consumption behaviors and their collective understanding of pangolins, which improve pangolin protection efforts around the globe.